2013
DOI: 10.1007/s13277-013-0689-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 genetic variants and susceptibility to hepatocellular carcinoma and HBV-related hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a highly aggressive cancer with few treatment options. Toll-like receptor 3 (TLR3) plays a key role in innate immunity and may affect the development of cancers. This study aimed to investigate whether TLR3 polymorphisms were associated with susceptibility to HCC. Two polymorphisms in the TLR3 gene, -976T/A and +1234C/T, were tested by polymerase chain reaction-restriction fragment length polymorphism in 466 HCC patients and 482 healthy controls. Results showed that the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 25 publications
2
36
1
1
Order By: Relevance
“…Genetic variations in TLR3 have been correlated with susceptibility to various diseases, including CHB and HCC. Previous studies reported that the TLR3 C1234T polymorphism was associated with increased susceptibility to CHB (Rong et al, 2013), as well as HCC (Li and Zheng, 2013). The present study demonstrated that the TLR3 rs3775290 polymorphism was associated with a decreased risk for CHB, HBV-related LC, and HCC.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Genetic variations in TLR3 have been correlated with susceptibility to various diseases, including CHB and HCC. Previous studies reported that the TLR3 C1234T polymorphism was associated with increased susceptibility to CHB (Rong et al, 2013), as well as HCC (Li and Zheng, 2013). The present study demonstrated that the TLR3 rs3775290 polymorphism was associated with a decreased risk for CHB, HBV-related LC, and HCC.…”
Section: Discussionsupporting
confidence: 71%
“…Genetic variations in TLR3 have been correlated with susceptibility to various diseases, including viral hepatitis and HCC (He et al, 2007;Ishizaki et al, 2008;Etem et al, 2011;Al-Qahtani et al, 2012;Sironi et al, 2012;Lee et al, 2013;Li and Zheng, 2013;Rong et al, 2013). However, little is known concerning TLR3 gene polymorphisms and HBVrelated CHB, LC, and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…HSC also undergo transformation into myofibroblasts, leading to increased production of extracellular matrix proteins; this process is a host-protective response, but causes scarring and liver fibrosis when dysregulated [79]. As noted above, TLR3 signalling has been implicated in host responses during HBV infection [40][41][42]. However, growing evidence suggests that TLR3 also contributes to the inactivation or death of activated HSC and Kupffer cells during liver injury, contributing to protective responses against liver damage [80] and fibrosis [81,82].…”
Section: Livermentioning
confidence: 99%
“…Tlr3 -/-mice displayed enhanced replication of HSV-1 in the CNS [38], and an increased susceptibility to HSV-2 infection in the CNS after vaginal inoculation [39]. In humans, TLR3 polymorphisms (C1234T, rs1879026 G/T) have also been linked to increased risk to chronic hepatitis B virus (HBV) infection and HBV-induced hepatocellular carcinoma [40,41], while the C13766T TLR3 polymorphism was suggested to be protective against HBV infection and HBV-related liver disease [42]. A study analysing Saudi Arabian patients with HBV infections reported a TLR3 single nucleotide polymorphism (rs1879026 G/T) that was found more frequently in HBV-infected patients [40].…”
Section: Role Of Tlr3 In Host Defencementioning
confidence: 99%
“…Рецептор, кодируемый этим геном, способен связывать двухцепочечную РНК [127]. При поиске взаимосвязи полиморфизма гена TLR3 с разви-тием злокачественных новообразований корреляции не обнаружено [119,[128][129][130][131][132][133][134][135][136].…”
Section: кумулятивная доля выжившихunclassified